An Artist in the Making: Stephen’s Search for Self-Identity in James Joyce’s A Portrait of the Artist as a Young Man - Seçil ERKOÇ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2018)
Tracing the transformation of Stephen Dedalus into an artist in the making, James Joyce’s A Portrait of the Artist as a Young Man presents the individual’s ongoing search for self-identity within the background of various notions such as religion, politics, Ireland, aesthetics, disillusionment and freedom. As an aspiring artist to be, Stephen goes through various stages and out of each stage he comes up with a new perception that enables him to broaden his horizon. While doing that, he rebels against the norms, and the codes of identity that he believes his home, his religion, and his country are trying to impose on him. As the hybrid quality of his name also testifies – bringing the religious (St. Stephen) and mythical (Deadelus) side by side – Stephen Dedalus takes the first step into a more unified vision which will enable him to see beyond the daily experience and turn it into an aesthetic inspiration. Accordingly, in addition to presenting an analysis of the thematic elements in the novel, it will also be attempted to illustrate the way in which Joyce points to an aesthetic and unified vision where the binaries give way to the encompassing vision of aesthetic unity.